INTERPRETATION OF ENERGY METHODS IN THE THEORY OF FRICTION AND WEAR FROM THE STANDPOINT OF CONTINUUM MECHANICS AND DISLOCATION THEORY - Malinovskyi, Yurii; Vlasenkov, Dmyro; Sytnyk, Serhii; Teroshyna, Svitlana; Oliinyk, Svitlana (Problems of Friction and Wear, 2023)
In modern tribotechnical calculations, a significant role is played by theories of friction and wear based on the energy of processes occurring on the outer layers of interacting parts. Thus, the energy approach allowed us to formulate the view that under dynamic loading of two elastic bodies, as a result of friction, part of the energy is reversible and goes to the development of elastic vibrations, another part of the energy of inelastic interaction of parts, at the molecular level, is redistributed to other types of energy and dissipated in the form of thermal energy into the environment, while the remaining energy, in the case of vibrations of surface layers, accumulates as an irreversible part of the potential energy in deeper layers of parts. This energy, when a certain threshold value is reached, contributes to the destruction of the surface and subsurface layers of the friction pair elements. Taking into account the temperature effects of friction has allowed a number of researchers to determine friction coefficients and forces based on the hypothesis of the formation of welding bridges during metal friction and their subsequent destruction. In addition, hypotheses about the diffusion of atoms during the friction of kinematic pair elements, as well as the hypothesis about the possibility of recrystallization of metals (and other materials) at room temperature, have become widespread. As a generalization of the results of the hypotheses considered, the author of [1] proved that the friction process has a dual nature and can be described by the molecular mechanical theory of friction and wear. The existence of a significant number of hypotheses and theories of friction and wear as physical phenomena is due to the convenience of the energy approach and the extreme complexity of the process itself. The proposed work is aimed at clarifying and, in some cases, simplifying tribotechnical and related thermal calculations.